The Evaluation of the Concept of Crime Geography in Turkey with Regards to the Law Enforcement Agency - (:unkn) unknown (MARMARA UNIV, 2017)
In this study, the relationship between crime and geography was investigated and the emphasis on the formation of crime and crime types of coalition conditions, the specific topics related to special police for the accomplices of crime, and the importance of crime partnership throughout the training of the personnel were mentioned. In this context, this study was carried out to examine the effects of the prosecution of criminal geography in the training of police forces, the profession of arts and professions of the success of police officers. The study, the interview and the document are the researches using the data collection methods and the qualitative process is observed when the perceptions and events combine realistic and holistic in the natural environment. A survey of the literature on the subject has been made and the information has been extracted. Later on, an interview was organized and a group of police officers were interviewed. In the interview, it was examined whether police officers understood crime concepts from the concept of geography, whether they received any education with crime geography in police school or vocational training courses. Establish geographical linking of accusing police officers, penalizing crimes from police officers. It was tried to prove the issue of the order of the forces of the army of the education of the geography of the crimes by determining the situations in terms of the ability of the police to establish relations with the crime and the crime and the geography.
Keywords: Crime; crime geography; police organization; geography teaching